2015
DOI: 10.1016/j.psi.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Applying affiliation social network analysis to understand interfaith groups

Abstract: a b s t r a c tThis study applies affiliation social network analysis to understand how interfaith groups provide resources to other community groups and link interfaith group members to resources for local community change. Based on a sample of 88 interfaith groups from across the U.S., affiliation social network analysis pictures show distinct patterns in how interfaith groups share resources with community groups and link members to community resources. Overall, results show how interfaith groups may be emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The reviewed literature coincides with the relevance of principles such as equality of differences, egalitarian dialogue, cultural intelligence, solidarity, and transformation to positively impact human agency. Although empirical research has examined the benefits of interreligious dialogue groups (Azdajic 2019;Gramstrup 2017;Todd et al 2015;Burgués et al 2016;Mondéjar and Villarejo 2017;Cerchiaro 2019;Ubani 2018;Knitter 2013), the creation of human agency has remained almost unexplored. There is scarce literature and evidence on how and why the implementation of such principles is needed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reviewed literature coincides with the relevance of principles such as equality of differences, egalitarian dialogue, cultural intelligence, solidarity, and transformation to positively impact human agency. Although empirical research has examined the benefits of interreligious dialogue groups (Azdajic 2019;Gramstrup 2017;Todd et al 2015;Burgués et al 2016;Mondéjar and Villarejo 2017;Cerchiaro 2019;Ubani 2018;Knitter 2013), the creation of human agency has remained almost unexplored. There is scarce literature and evidence on how and why the implementation of such principles is needed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In consequence, it is particularly relevant in studies of community psychology and in psychosocial interventions. As we show in this monograph, networks allow to detect patterns of collaboration that are not perceived intuitively (Todd et al, 2015), serve to examine the mutual influence of individual community organizations and networks of interorganizational collaboration (Faust et al, 2015;Menger et al, 2015;Rana & Allen, 2015), facilitate the dissemination of evidencebased practices among professionals of the intervention , and are a tool for intervention by themselves (Corlew et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this monograph, we collect a number of articles that make innovative contributions to social and community intervention using social network analysis. Following the index of this volume, we read: a study that assesses the impact of collaborative networks of community organizations in implementing effective interventions (Faust, Christens, Sparks, & Hingeldorf, 2015); an application of visualization of large relational databases to improve communication between professionals (Corlew, Keener, Finucane, Brewington, & Nunn-Crichton, 2015); an analysis of affiliation networks that identifies two types of interfaith groups depending on how the organizations exchange resources (Todd, Houston, & Suffrin, 2015); an assessment of the role of strong ties, which are developed across multiple types of relationships, between entities that form a coalition (Menger, Stallones, Cross, Henry, & Chen, 2015); a description of the influence of the Family Violence Councils network in the practice of the organizations that are part of them (Rana & Allen, 2015); a theoretical review of the chains of intermediaries between researchers and professionals of intervention ; and a survey on the variability of personal networks depending on metropolitan mobility (Maya-Jariego & Holgado, 2015).…”
Section: Overview Of the Issuementioning
confidence: 99%
“…Furthermore, we have shown how the projects have, through collaboration, achieved objectives that would have been impossible on their own. Applying appropriate analysis tools to the network has confirmed that within development networks, social capital is productive (Bagnasco, 2002), and that this productivity is achieved through the actors' interactions around the available network resources (Kadushin, 2004;Todd, Houston, & Suffrin, 2015). Furthermore, we can confirm the validity of analyzing development networks with a combination of quantitative and qualitative research methods: combining quantitative data, analyzed through network algorithms to allow the visualization of networks, and qualitative data, to complement the quantitative information and to explain observed dynamics, is a common practice in network-evaluation (Frechtling & Sharp, 1997) that seems to fit well within development co-operation.…”
Section: O411mentioning
confidence: 99%